2008
DOI: 10.1029/2007jd008589
|View full text |Cite
|
Sign up to set email alerts
|

A physical model to estimate snowfall over land using AMSU‐B observations

Abstract: In this study, we present an improved physical model to retrieve snowfall rate over land using brightness temperature observations from the National Oceanic and Atmospheric Administration's (NOAA) Advanced Microwave Sounder Unit-B (AMSU-B) at 89 GHz, 150 GHz, 183.3±1 GHz, 183.3±3 GHz, and 183.3±7 GHz. The retrieval model is applied to the New England blizzard of March 5, 2001 which deposited about 75 cm of snow over much of Vermont, New Hampshire, and northern New York.In this improved physical model, prior re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 64 publications
(78 reference statements)
0
44
0
Order By: Relevance
“…Passive microwave remote sensing has the potential for discriminating between rainfall and snowfall because microwave radiation emitted by the Earth's surface propagates through all but the densest precipitating clouds, meaning that radiation at microwave wavelengths directly interacts with hydrometeors within clouds (Olson et al, 1996;Ardanuy, 1989). However, the remote sensing of precipitation in microwave wavelengths and the development of operational algorithms is dominated by research focused on rainfall (Arkin and Ardanuy, 1989); by comparison, snowfall detection and observation has received less attention (Noh et al, 2009;Kim et al, 2008). This is partly explained by examining the physical processes within clouds that attenuate the microwave signal.…”
Section: Space-based Remote Sensing Observationsmentioning
confidence: 99%
“…Passive microwave remote sensing has the potential for discriminating between rainfall and snowfall because microwave radiation emitted by the Earth's surface propagates through all but the densest precipitating clouds, meaning that radiation at microwave wavelengths directly interacts with hydrometeors within clouds (Olson et al, 1996;Ardanuy, 1989). However, the remote sensing of precipitation in microwave wavelengths and the development of operational algorithms is dominated by research focused on rainfall (Arkin and Ardanuy, 1989); by comparison, snowfall detection and observation has received less attention (Noh et al, 2009;Kim et al, 2008). This is partly explained by examining the physical processes within clouds that attenuate the microwave signal.…”
Section: Space-based Remote Sensing Observationsmentioning
confidence: 99%
“…Unfortunately, routine surface measurements of snow are scarce in remote regions where snowfall frequently occurs, and these locales are also largely devoid of ground-based remote sensing observations that could provide useful information about frozen precipitation. Therefore, satellite-based microwave remote sensing remains the most viable option to obtain global snowfall information, and increasing attention is being dedicated to retrieve properties of snow via passive, active, and combined microwave observations (e.g., SkofronickJackson et al 2004;Noh et al 2006;Kim et al 2007;Liu 2008a;Grecu and Olson 2008). These recent research avenues are especially critical to prepare for the Global Precipitation Measurement (GPM) mission that is scheduled to launch early in the next decade and will include coincident active and passive measurements at higher latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the presence of the non-Rayleigh effects, which introduce some dependence on the particle shape and orientation, the masssize relationship, is still a key factor. This can be seen in the parameterization of the W-band backscattering as a function of mass proposed by Kim [2004]. Similarly, Zhang [2004] suggested that the most important factor controlling the backscattering intensity of random oriented crystal is the ratio of the ice volume equivalent radius to the maximum dimension D; this ratio is directly related to the density.…”
Section: Modified Mass-size Relationshipmentioning
confidence: 93%
“…Some investigators assume the aspect ratios fixed, sizeindependent, while some of them use the published empirical dimensional relations [Jayaweera and Cottis, 1969;Auer and Veal, 1970;Heymsfield, 1972;Hobbs et al, 1974;Jayaweera and Ohtake, 1974;Mitchell and Arnott, 1994;Matrosov et al, 1996]. However, there are differences between the empirical relations for the same ice crystal habit, as shown in Kim [2004]. The most used are the dimensional relationships published by Auer and Veal [1970], derived from measurements at a mountain laboratory, and hence, their validity for high cloud particles may be questionable.…”
Section: Appendix B: Projected Area Dimensional Relationshipmentioning
confidence: 99%